Mineral composition characteristics of radiocesium sorbed and transported sediments within the Tomioka river basin in Fukushima Prefecture. (January 2020) - Hagiwara, Hiroki; Konishi, Hiromi; Nakanishi, Takahiro; Fujiwara, Kenso; Iijima, Kazuki; Kitamura, Akihiro
Abstract: The deposited radiocesium in the Fukushima river basin is transported in the river systems by soil particles and redistributed in the downstream areas. Although predicting the behaviors of minerals that adsorb radiocesium and of radiocesium dissolved in river water within the river systems is essential, the dominant mineral species that adsorb radiocesium have not yet been comprehensively identified. We identify herein such mineral species by investigating the 137 Cs distribution and the mineral species in each size fraction that are found in the bedload sediments from an upstream reservoir to an estuary within the Tomioka river basin located east of Fukushima Prefecture in Japan. In the fine sand sediment, which is the dominant fraction in terms of the 137 Cs quantity in the river bedload, the 137 Cs concentrations of the felsic and mafic minerals are comparable to that of micas. The mafic minerals contain 62% of the 137 Cs in the fine sand fraction in the upstream area, while the felsic minerals contain the highest quantities of 137 Cs in the downstream area. These results suggest that the quantification of the mineral species and the 137 Cs concentration of each size fraction are critically important in predicting the behaviors of the minerals and radiocesium within the Fukushima river basin in the future. Highlights: The fine-sand fraction of the Tomioka river bedload predominantly contained 137 Cs. Not only micas but felsic and mafic minerals could contribute to radiocesium sorption. The 137 Cs sorption on the micas was relatively low.